2007
DOI: 10.1073/pnas.0702620104
|View full text |Cite
|
Sign up to set email alerts
|

Cernunnos/XLF promotes the ligation of mismatched and noncohesive DNA ends

Abstract: DNA repair ͉ nonhomologous end-joining ͉ V(D)J recombinationT he nonhomologous end-joining (NHEJ) pathway is conserved in eukaryotes, from yeast to humans. Without requiring homologous DNA, NHEJ repairs DNA double-strand breaks produced by xenobiotic agents, such as topoisomerase II inhibitors and ionizing radiation, or by the cellular pathway for V(D)J recombination of the immunoglobulin genes (1). Even when the structure of the DNA ends prevents ligation, NHEJ processes the ends and repairs the breaks with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
155
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(169 citation statements)
references
References 25 publications
12
155
0
2
Order By: Relevance
“…The crystal structure of the L4-X4-Cernunnos complex with the fulllength proteins should help to clarify the binding mode of the complete ligation complex. DSB repair studies in the presence or absence of Cernunnos have shown that Cernunnos promotes DNA end ligation by the L4-X4 complex (25,33). From our observation, we propose that the oligomerization of the X4-Cernunnos complex could be a mechanism to facilitate the recruitment of two or more L4-X4 complexes to DNA DSB repair points (Fig.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The crystal structure of the L4-X4-Cernunnos complex with the fulllength proteins should help to clarify the binding mode of the complete ligation complex. DSB repair studies in the presence or absence of Cernunnos have shown that Cernunnos promotes DNA end ligation by the L4-X4 complex (25,33). From our observation, we propose that the oligomerization of the X4-Cernunnos complex could be a mechanism to facilitate the recruitment of two or more L4-X4 complexes to DNA DSB repair points (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…The association between Cernunnos and L4-X4 complex is mediated primarily through an interaction with X4 (14), although a weak interaction with L4 has also been reported (16). Cernunnos stimulates the ligase activity of the L4-X4 complex (20,21,(23)(24)(25) and seems particularly important for the ligation of mismatched or noncohesive DNA ends (25,26). Like X4, Cernunnos is a homodimer (27,28).…”
mentioning
confidence: 99%
“…These proteins are structurally similar to and interact with the yeast Lif1 and human XRCC4 subunit of the DNA ligase IV complex (20 -23, 25, 28, 30, 35). In addition, XLF enhances joining by DNA ligase IV-XRCC4 of both matched and mismatched DNA ends (31)(32)(33)(34)46). Using a combination of molecular genetic and biochemical approaches, we have demonstrated that Nej1 not only contributes to the final ligation step of NHEJ but also plays a critical role in the initiation of the NHEJ pathway.…”
Section: Discussionmentioning
confidence: 95%
“…The gene was cloned independently from immunodeficient patients that showed radio sensitivity (Buck et al, 2006) and by a yeast 2-hybrid screen for proteins that interact with XRCC4 (Ahnesorg et al, 2006). It stimulates NHEJ, which appears to be mainly important for noncomplementary DNA ends, but does not seem to be an absolute requirement for the majority of DSBs (Gu et al, 2007;Tsai et al, 2007;Wu et al, 2007).…”
Section: Dna Ligase IV Xrcc4 and Xlf/cernunnosmentioning
confidence: 99%